Aspek-aspek hukum dalam perbankan & perasuransian Syariah di Indonesia - Dewi, Gemala, 1964- (Jakarta : Kencana, 2004)
Legal aspects of Islamic banking and insurance in Indonesia
Includes bibliographical references (p. [233]-235)
Keywords: Banks and banking -- Indonesia -- Law and legislation; Insurance -- Indonesia -- Law and legislation; Banks and banking -- Indonesia -- Religious aspects -- Islam; Insurance -- Indonesia; Insurance -- Religious aspects -- Islam